Perspectives of teacher educators on the challenges of training technical and vocational education teachers in Ethiopia - Kebede, Amarech; Asgedom, Amare (Bahir Dar Journal of Education, 2024)
Shortage of qualified teachers is a critical problem in the Technical and Vocational Education and Training (TVET) sector. This study investigates the barriers that hinder the preparation of competent TVET teachers in Ethiopia. A qualitative case study involving 20 purposively selected teacher educators was used. The study revealed numerous challenges including weak student admission criteria, a lack of teacher competency standards, irrelevant curriculum, theory-focused training, limited resources, ineffective quality assurance system, leadership issues, and gaps in teacher educators’ practical and pedagogical skills, industry experience, interest, and motivation. The study concluded that TVET teacher training is beset by various limitations and urgently requires reform. In this regard, it is critical to attract high-quality and motivated candidates, establish competency standards, adapt the curriculum to meet the specific needs of TVET teachers, involve industries in the training process, and enhance the competencies of teacher educators through industry placements.